Assessment of a Scoring System to Predict Difficult Laparoscopic Cholecystectomy - Sigdel, Prem R; Subedi, Nirajan; Phuyal, Suman; Pokharel, Ashik; Ghimire, Bikal; Singh, Yogendra P (Journal of Institute of Medicine Nepal, 2020)
Introduction Laparoscopic cholecystectomy (LC) has become the procedure of choice for management of symptomatic gallstone disease. It would be useful to have some reliable predictive factors for conversion in LC. Our aim is to predict difficult laparoscopic cholecystectomy preoperatively by using a scoring system.MethodsA total of 136 patients were included. The parameters considered for this study were old age, male sex, history of hospitalization, obesity, abdominal surgery scar, palpable gall bladder, gall bladder wall thickness, pericholecystic collection and impacted stone.ResultsAmong 136 cases, 70.6% were easy, 24.3% were difficult and 5.1% were very difficult intraoperatively. The factors like age >50 years, history of hospitalization for acute cholecystitis, previous abdominal surgery, palpable gall bladder, wall thickness >4mm and impacted stone were found statistically significant in predicting difficult LC. The preoperative scoring is statistically and clinically a good test for predicting the difficult LC (area under the curve = 0.824) with sensitivity of the test being 82.3% and specificity 72.7%. Conversion rate was 3.67%.ConclusionThe factors like age >50 years, history of hospitalization for acute cholecystitis, previous abdominal surgery, palpable gall bladder, wall thickness >4 mm and impacted stone are the preoperative predictors of difficult LC.